2022
DOI: 10.3389/fonc.2022.860257
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Implementation of Neurosurgical Enhanced Recovery After Surgery Protocol for Gliomas in Patients Undergoing Elective Craniotomy

Abstract: ObjectiveTo design a multidisciplinary enhanced recovery after surgery (ERAS) protocol for glioma patients undergoing elective craniotomy and evaluate its clinical efficacy and safety after implementation in a tertiary neurosurgical center in China.MethodsERAS protocol for glioma patients was developed and modified based on the best available evidence. Patients undergoing elective craniotomy for treatment of glioma between September 2019 to May 2021 were enrolled in a randomized clinical trial comparing a conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…These elements include preoperative patient education, nutritional optimization, minimally invasive surgical techniques, standardized anesthetic management, multimodal analgesia, and standardized postoperative care protocols including early mobilization. 8,[21][22][23] Studies have shown that patients under these protocols experience no increase in postoperative complications, benefit from shorter hospital stays, and report enhanced satisfaction. 5,6,8,11 Spine Surgery ERAS protocols in spine surgery, especially procedures involving lumbar and cervical regions, have been reported to reduce postoperative pain, result in fewer complications, and reduce hospital lengths of stay.…”
Section: Craniotomymentioning
confidence: 99%
See 4 more Smart Citations
“…These elements include preoperative patient education, nutritional optimization, minimally invasive surgical techniques, standardized anesthetic management, multimodal analgesia, and standardized postoperative care protocols including early mobilization. 8,[21][22][23] Studies have shown that patients under these protocols experience no increase in postoperative complications, benefit from shorter hospital stays, and report enhanced satisfaction. 5,6,8,11 Spine Surgery ERAS protocols in spine surgery, especially procedures involving lumbar and cervical regions, have been reported to reduce postoperative pain, result in fewer complications, and reduce hospital lengths of stay.…”
Section: Craniotomymentioning
confidence: 99%
“…8,[21][22][23] Studies have shown that patients under these protocols experience no increase in postoperative complications, benefit from shorter hospital stays, and report enhanced satisfaction. 5,6,8,11 Spine Surgery ERAS protocols in spine surgery, especially procedures involving lumbar and cervical regions, have been reported to reduce postoperative pain, result in fewer complications, and reduce hospital lengths of stay. 7,24 Furthermore, the Society for Neuroscience in Anesthesiology and Critical Care (SNACC) produced guidelines for complex spine surgery 25 that align with current ERAS recommendations.…”
Section: Craniotomymentioning
confidence: 99%
See 3 more Smart Citations